Cognitive restriction accentuates the increased energy intake response to a 10-month multidisciplinary weight loss program in adolescents with obesity. (1st March 2019) - Miguet, M.; Masurier, J.; Chaput, J.P.; Pereira, B.; Lambert, C.; Dâmaso, A.R.; Courteix, D.; Duclos, M.; Boirie, Y.; Thivel, D.
Abstract: Background: Multidisciplinary interventions have shown some merits in weight reduction strategies in youth, however, their impact on subsequent daily energy intake remains largely unknown. The aim of the present study was to evaluate the nutritional responses to a 10-month multidisciplinary intervention among adolescents with obesity, in relation to their eating behavior characteristics. Methods: Thirty-five adolescents (mean age: 13.4 ± 1.2 years) with obesity took part in a 10-month residential multidisciplinary weight loss program. Anthropometric measurements, body composition (dual-energy X-ray absorptiometry), 24-h ad libitum energy intake (weighted), eating behaviors (Dutch Eating Behavior Questionnaire) and appetite sensations (Visual Analogue Scales) were assessed on three occasions: at their arrival in the institution (T0), after 5 months (T1), and at the end of the 10-month program (T2). Results: The mean weight loss reached 11% of the adolescents' initial body weight, with an important inter-individual variability (−25% to +3% of their initial body weight). Results revealed sex differences change, with boys showing a higher decrease in fat mass percent and increase in fat-free mass compared with girls. Weight loss was accompanied by a significant decrease in emotional (−8.3%, p < 0.05) and external (−14.8%, p < 0.001) eating scores and a significant increase in 24-h ad libitum energy intake (+246 kcal, p < 0.001). The observed subsequent increased 24-h ad libitum energy intake at T2 compared to T0 was significantly higher in cognitively restrained eaters (+492 kcal) compared to unrestrained eaters (+115 kcal, p = 0, 015). Dietary restraint score at baseline was inversely correlated with the percentage of weight loss (r = −0.44, p = 0.010). Conclusion: A 10-month multidisciplinary weight loss intervention induced an increase in 24-h ad libitum energy intake compared to baseline, especially in cognitively restrained eaters. Moreover, initially cognitively restrained eaters tended to lose less body weight compared to unrestrained ones. These findings suggest that cognitive restriction may be a useful eating behavior characteristic to consider as a screening tool for identifying adverse responders to weight loss interventions in youth.